Kinetics of Supercritical CO2 Extraction from Burrito (Aloysia polystachya) Leaves and Sucupira-Preta (Bowdichia virgilioides) Seeds - Gabrielle Vaz Vieira; Michel Rubens dos Reis Souza; Carlos Toshiyuki Hiranobe; José Eduardo Goncalves; Cristiane Mengue Feniman Moritz; Otávio Akira Sakai; Leila Maria Sotocorno e Silva; Michael Jones da Silva; Erivaldo Antônio da Silva; Renivaldo José dos Santos; Edson Antônio da Silva; Lucio Cardozo-Filho; et al. (Separations)
This study investigated the application of supercritical carbon dioxide (CO2) for the extraction of essential oils from plant materials with anxiolytic potential, focusing on the leaves of burrito (Aloysia polystachya) and the seeds of sucupira-preta (Bowdichia virgilioides). The supercritical extraction technique was chosen for its ability to produce high-purity extracts without residual solvents and to reduce the environmental impact. This study evaluated the influence of temperature (40 °C, 50 °C, and 60 °C) and pressure (22 MPa, 25 MPa, and 28 MPa) on extraction efficiency using a 22 factorial design with triplicates at the central point. The maximum yields were 1.2% for burrito leaves and 4.2% for sucupira-preta seeds. Despite their relatively low yields, the extracts contained a diverse range of chemical compounds, including fatty acids (oleic, linoleic, and palmitic acids), squalene, β-carotene, vitamin E, and other bioactive molecules with antioxidant, anti-inflammatory, and immunomodulatory properties. Statistical analysis demonstrated that pressure was the most influential factor affecting yield, whereas temperature played a secondary role. The Sovová kinetic model provided a good fit for the extraction curves, with determination coefficients (R2) above 0.95, thus validating the efficiency of the method. These results highlight the pharmaceutical potential of these extracts, particularly for therapeutic and anxiolytic purposes.